Dynamic 4 ENF test for a strain rate dependent mode II interlaminar fracture toughness characterization of unidirectional carbon fibre epoxy composites. (October 2016) - Zabala, H.; Aretxabaleta, L.; Castillo, G.; Aurrekoetxea, J.
Abstract: A dynamic 4ENF testing procedure has been proposed to characterize the influence of loading rate on mode II fracture interlaminar toughness of a unidirectional composite material. The stable crack growth accomplished by the proposed dynamic 4ENF procedure allows achievement of the R -curves and the in-situ compliance calibration of each specimen. This enables performance of a monotonic dynamic test and presents a great advantage for the dynamic interlaminar characterization of the composite material. The dynamic G IIC -s values obtained are similar to those determined by quasi-static loading conditions, which suggests that the proposed testing procedure is able to determine accurately the dynamic G IIC of a composite material. However, for the tested material and within the analysed loading rate range, both the determined R -curves and G IIC values do not show any clear sign of loading rate dependence.